Implementation of Law Enforcement by the Food Task Force of The Criminal Office of the Police in Tackling Rice Adulty Ahead of National Religious Days - Muhammad Ardiriansyah; Agus Sumartono (LP2M IAIN Palopo, 2026)
Staple foods, especially rice, are the main needs of the Indonesian people. The availability and stability of rice prices are crucial issues, especially ahead of National Religious Holidays (HBKN), such as Eid al-Fitr, Christmas, and New Year. During these periods, demand for rice increases significantly, while distribution is often disrupted by hoarding, speculation, and the circulation of rice that does not meet quality standards. The purpose of this study is to assess the extent of the implementation of law enforcement against violations of adulterated rice ahead of national religious holidays, the method in this study uses a qualitative descriptive approach. This study shows that ahead of National Religious Holidays (HBKN), the National Police Food Task Force increases supervision and law enforcement against rice Bapokting practices through distribution monitoring, warehouse inspections, market operations, and counseling to business actors. Law enforcement is carried out preventively and repressively, but its effectiveness is still limited by administrative constraints, limited personnel, and the level of compliance of business actors. The conclusion of this study is to prevent and take action against the practice of Bapokting, the National Police Food Task Force conducts price and stock monitoring, joint operations, enforcement of administrative and criminal sanctions, and outreach to traders and the public. These steps aim to maintain price stability and rice availability, while increasing legal compliance ahead of HBKN.